A review of recent research in EFL motivation: Research trends, emerging methodologies, and diversity of researched populations. (December 2021) - Vonkova, Hana; Jones, Jane; Moore, Angie; Altinkalp, Irem; Selcuk, Hasan
Abstract: The increasing interest in English as a foreign language (EFL) across the globe has necessitated learning opportunities that engage and sustain students' motivation to learn English. This paper aims to provide an analysis of trends in EFL motivation between 2016 and 2020. While examining 90 studies published during this time frame, we have focused on an overview of methodologies, theories, and backgrounds of researched populations. We have also aimed to summarize the key findings of the literature in order to discuss the emergent themes in current EFL motivation research. Hence, this paper offers a comprehensive analysis and synthesis of recent EFL motivation research trends. Although 24 countries and economies were represented, many studies came from Taiwan and China. Furthermore, most of the studies featured socioeconomically privileged students and students at the higher levels of education, with few mentions of disadvantaged populations. We found extensive use of technology, through which we can identify a viable path for enhancing language learning, teaching, and future research. This review highlights the need for sustainable interventions and studies with diverse populations in the expanding field of EFL. Highlights: 90 studies on motivation in English as a foreign language learning were reviewed. There was limited evidence of innovation in methodological approaches. Use of technology was found to enhance language learning motivation and instruction. The few qualitative studies provided nuanced insight into learners' L2 self-images. Research needs to include more cross-national, diverse, and inclusive populations.